1996
DOI: 10.1136/gut.39.6.852
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of endoscopic stenting alone with stenting and radiotherapy in non-resectable cholangiocarcinoma.

Abstract: Background and Aims-Radiotherapy has been reported to be of benefit in prolonging the survival of patients with cholangiocarcinoma. This study examined whether radiotherapy in addition to endoscopic stenting improved survival. Subjects-56 patients with obstructive jaundice due to histologically confirmed non-resectable cholangiocarcinoma. Methods-A retrospective analysis of these patients who were treated either with endoscopic biliary stenting followed by external beam radiotherapy and internal iridium-192 br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 30 publications
0
71
0
4
Order By: Relevance
“…One study found a median survival of 10 months (range, 4 to 75 months) with external-beam irradiation combined with internal irridium 192 brachytherapy in 28 patients compared with 7 months (range, 1 to 29 months) in a similar number of patients managed by endoscopic stenting. 5 In another study, median survival using the combination of external-beam irradiation, transcatheter irridium, and chemotherapy with fluorouracil was 13 months (range, 8 months to 9 years). 6 The apparent benefits of local irradiation have not been translated into survival benefits because of recurrent disease within the liver or abdominal cavity.…”
Section: Treatmentmentioning
confidence: 99%
“…One study found a median survival of 10 months (range, 4 to 75 months) with external-beam irradiation combined with internal irridium 192 brachytherapy in 28 patients compared with 7 months (range, 1 to 29 months) in a similar number of patients managed by endoscopic stenting. 5 In another study, median survival using the combination of external-beam irradiation, transcatheter irridium, and chemotherapy with fluorouracil was 13 months (range, 8 months to 9 years). 6 The apparent benefits of local irradiation have not been translated into survival benefits because of recurrent disease within the liver or abdominal cavity.…”
Section: Treatmentmentioning
confidence: 99%
“…EMSs are inserted percutaneously [61][62][63] or endoscopically [59,64] . Biliary stent placement combined with local tumor therapy, such as brachytherapy, extra-radiation therapy, or arterial infusion chemotherapy, can prolong the survival time of patients with malignant biliary obstruction [65][66][67][68] . Mezawa et al [69] developed a new PTBD tube coated with carboplatin.…”
Section: Palliative Therapymentioning
confidence: 99%
“…2,5 Survival with nonresectable tumor lasts for a median of 3 months without intervention and 4 to 6 months with biliary drainage. [11][12][13][14][15] Given the longer hospitalization time, the adverse effects, and the marginal life extension with anticancer therapies, 2,[16][17][18] usual palliation still is biliary drainage only.…”
mentioning
confidence: 99%